2014
DOI: 10.1093/intimm/dxu074
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related disease and its pathogenesis—cross-talk between innate and acquired immunity

Abstract: IgG4-RD, a novel disease involving many immune-system components

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 97 publications
(129 reference statements)
4
65
1
1
Order By: Relevance
“…The serum CRP level observed on admission (12 mg/dL) in our patient was too high to be indicative of IgG4-RD, as most patients with IgG4-RD show relatively low titers of CRP (15). However, among the three reported cases of IgG4-related arthritis (10)(11)(12), the CRP levels, which were described in two patients (11,12), were both elevated (2.4 and 8 mg/dL, respectively).…”
Section: Discussioncontrasting
confidence: 61%
“…The serum CRP level observed on admission (12 mg/dL) in our patient was too high to be indicative of IgG4-RD, as most patients with IgG4-RD show relatively low titers of CRP (15). However, among the three reported cases of IgG4-related arthritis (10)(11)(12), the CRP levels, which were described in two patients (11,12), were both elevated (2.4 and 8 mg/dL, respectively).…”
Section: Discussioncontrasting
confidence: 61%
“…Although the essential role of the IgG4 antibody in the pathogenesis of IgG4-RD remains unclear, increased serum IgG4 levels and tissue infiltration by IgG4-positive plasma cells are thought to be key events in IgG4-RD (2,3,18) This case may reveal the dysregulation of B lymphocytes, which may be the underlying pathologic cause of both IgG4-RD and cryoglobulinemia; this would be consistent with the past history of lymphoma. An important factor for B lymphocyte survival and proliferation is B cell-activating factor (BAFF).…”
Section: Discussionsupporting
confidence: 53%
“…An important factor for B lymphocyte survival and proliferation is B cell-activating factor (BAFF). This factor is known to regulate the maturation and survival of B cells and mediate CD40 ligandindependent antibody production and induction of IgG4 class switching in the presence of IL-4 (18,19). Studies have shown that serum concentrations of BAFF and its homolog APRIL (a proliferation-inducing ligand) were significantly higher in patients with IgG4-RD than in healthy individuals (20,21) and that serum BAFF levels decrease following therapy (20).…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, we examined CpG methylation of MST1 and RASSF5C in IgG4-related autoimmune pancreatitis (AIP). IgG4-related AIP is characterized by a frequent elevation of serum IgG4 and infiltration of IgG4-positive plasma cells into the pancreas and other organs, therefore it is categorized as a pancreatic manifestation of a novel systemic IgG4-related disease (IgG4-RD) [17,18]. IgG4-RD includes a wide variety of diseases that were formerly diagnosed as Mikulicz's disease, hypophysitis, Riedel thyroiditis, interstitial pneumonitis, interstitial nephritis, prostatitis, lymphadenopathy retroperitoneal fibrosis, inflammatory aortic aneurysm, and inflammatory pseudotumor.…”
Section: Introductionmentioning
confidence: 99%